Future Career anxiety & Its Relation with Self- Efficacy among the General Education Diploma Students in South Al Batinah Governorate in the Sultanate of Oman - Almuqbali, Ali Humaid Saif; Al- Khawaja, Abdel Fattah Mohammed Saeed (Journal of Educational and Psychological Sciences, 2020)
The study aims to identify the relationship between future career anxiety & self- efficacy among students of the General Education Diploma in South al Batinah Governorate in Oman. A descriptive research design used; In order to achieve the objectives of the study, two scales were applied: the future career Anxiety Scale & Self- Efficacy Scale on a sample of 488 male & female students. The results of the study showed that the level of professional career anxiety & level of self- efficacy among students are in general moderate. And there is a negative statistically correlation between future career anxiety & self- efficacy. The study recommends conducting counseling programs to reduce the level of future career anxiety among diploma students ([1]) هذا البحث مستل من رسالة ماجستير إرشاد وتوجيه، جامعة نزوى، للطالب علي المقبالي، وإشراف د.عبد الفتاح الخواجه، 2019م.